The Effect of Multiliteracy Learning Model on Critical Thinking Ability of Fourth-Grade Students at SDN 19 Sitiung - Hasibuan, Sukriadi; Karisna, Feby; Fitri , Alchonity Harika; Yana, Dwi Novitri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the effect of the multiliteracy learning model on the critical thinking ability of fourth-grade students at SDN 19 Sitiung. The problem identified is the low critical thinking ability of students due to a lack of self-confidence, difficulties in decision-making, and challenges in problem-solving. This research uses an experimental method with a one-group pretest-posttest design. The sample consists of 26 students. The instrument used was a validated and reliable critical thinking questionnaire. The results show that the average pretest score of 61.4 increased to 72.7 in the posttest. The hypothesis test using paired samples t-test yielded a significance value of 0.000 < 0.05, indicating that the multiliteracy learning model significantly affects the improvement of students' critical thinking skills. This model has been proven to make students more active, confident, and able to think critically.